A unique nanoparticulate TLR9 agonist enables a HA split vaccine to confer FcγR-mediated protection against heterologous lethal influenza virus infection. (7th December 2018) - Yamamoto, Takuya; Masuta, Yuji; Momota, Masatoshi; Kanekiyo, Masaru; Kanuma, Tomohiro; Takahama, Shoukichi; Moriishi, Eiko; Yasutomi, Yasuhiro; Saito, Takashi; Graham, Barney S; Takahashi, Yoshimasa; Ishii, Ken J
Abstract : A nanoparticle adjuvant enhances protection against heterologous influenza strains Abstract: The development of a universal influenza vaccine that can provide a robust and long-lasting protection against a broader range of influenza virus strains is a global public health priority. One approach to improve vaccine efficacy is to use an adjuvant to boost immune responses to the target antigens; nevertheless, the role of adjuvants in the context of influenza vaccines is not fully understood. We have previously developed the K3-schizophyllan (SPG) adjuvant, which is composed of nanoparticulated oligodeoxynucleotides K3, a TLR9 agonist, with SPG, a non-agonistic β-glucan ligand of Dectin-1. In this study, K3-SPG given with conventional influenza hemagglutinin (HA) split vaccine (K3-SPG HA) conferred protection against antigenically mismatched heterologous virus challenge. While K3-SPG HA elicited robust cross-reactive HA-specific IgG2c and CD8 T-cell responses, CD8 T-cell depletion had no impact on this cross-protection. In contrast, K3-SPG HA was not able to confer protection against heterologous virus challenge in FcRγ-deficient mice. Our results indicated that FcγR-mediated antibody responses induced by the HA antigen and K3-SPG adjuvant were important for potent protection against antigenically mismatched influenza virus infection. Thus, we demonstrated that the K3-SPG-adjuvanted vaccine strategy broadens protective immunity against influenza and provides a basis for the development of next-generation influenza vaccines.